The Concept of Children's Language Development in Elementary Schools/Madrasah Ibtidaiyah - Auliya Fia; Suyadi Suyadi; Nelsa Putri Ayu; Rizka Febriyani Awliyah (STAI Ma'had Aly Al-Hikam Malang, 2020)
This study aims to examine more deeply the concepts, theories, aspects, influencing factors and steps in developing children's language at the primary school / madrasah level. The type of research used is library research with a qualitative approach. Data collection techniques in this study are documentation studies, namely data collection techniques by analyzing the contents of documents related to the problem under study. Analysis of the data used in this research is content analysis. The results show that language development can be combined with what happens in several years of child development. However, on the other hand there are several factors that can affect children's language development such as the child's age, environmental conditions, children's intelligence, family's socioeconomic status, and physical condition.